SlTPL1 Silencing Induces Facultative Parthenocarpy in Tomato - He, Mi; Song, Shiwei; Zhu, Xiaoyang; Lin, Yuxiang; Pan, Zanlin; Chen, Lin; Chen, Da; Hu, Guojian; Huang, Baowen; Chen, Mengyi; Wu, Caiyu; Chen, Riyuan; et al. (Frontiers in Plant Science, 2021)
Facultative parthenocarpy is of great practical value. However, the molecular mechanism underlying facultative parthenocarpy remains elusive. Transcriptional co-repressors (TPL) act as a central regulatory hub controlling all nine phytohormone pathways. Previously, we proved that SlTPLs participate in the auxin signaling pathway by interacting with auxin/indole acetic acid (Aux/IAAs) in tomato; however, their function in fruit development has not been studied. In addition to their high expression levels during flower development, the interaction between SlTPL1 and SlIAA9 stimulated the investigation of its functional significance via RNA interference (RNAi) technology, whereby the translation of a protein is prevented by selective degradation of its encoded mRNA. Down-regulation of SlTPL1 resulted in facultative parthenocarpy. Plants of SlTPL1-RNAi transgenic lines produced similar fruits which did not show any pleiotropic effects under normal conditions. However, they produced seedless fruits upon emasculation and under heat stress conditions. Furthermore, SlTPL1-RNAi flower buds contained higher levels of cytokinins and lower levels of abscisic acid. To reveal how SlTPL1 regulates facultative parthenocarpy, RNA-seq was performed to identify genes regulated by SlTPL1 in ovaries before and after fruit set. The results showed that down-regulation of SlTPL1 resulted in reduced expression levels of cytokinin metabolism-related genes, and all transcription factors such as MYB, CDF, and ERFs. Conversely, down-regulation of SlTPL1 induced the expression of genes related to cell wall and cytoskeleton organization. These data provide novel insights into the molecular mechanism of facultative tomato parthenocarpy and identify SlTPL1 as a key factor regulating these processes.